Sulfur Dioxide Preserves Superoxide Dismutase and Catalase Activities in Acute Kidney Injury - Biabanian1, Elham; Khaksari1, Mehdi; Norouzi1, Pirasteh; Khastar1*, Hossein (Shahroud Journal of Medical Sciences, 2017)
Background: Acute kidney injury (AKI) is a major clinical problem in situations such as shock, sepsis, and kidney transplantation, and also occurs as a side effect of some drugs. Gentamicin (GM) is an effective antibiotic against severe gram-negative infections. However, it can produce AKI in humans. Reactive oxygen species (ROS) have been proposed as the causative factor for the renal side effects of GM. This study was performed to investigate the protective role of sulfur dioxide (SO2) against GM-induced acute kidney injury in rats.Methods: Male Wistar rats were randomly assigned to one of the following groups: 1, sham group; 2, GM group (100 mg/kg i.p. for 7 days); and 3, GM+SO2 group (5 μg/kg i.p. for 7 days). On day 8, renal tissues were collected for oxidative stress assessment. To compare the groups, superoxide dismutase (SOD) and catalase (CAT) in renal tissue were measured.Results: GM caused significant acute kidney injury as demonstrated by the increase in BUN and creatinine levels in plasma. The decrease in renal tissue SOD and CAT levels revealed that oxidative stress occurred in the kidney. In the GM+SO2 group, SO2 prevented GM-induced reduction in SOD and CAT levels to some extent.Conclusions: These findings suggest that SO2 partly protects the kidneys from GM-induced nephrotoxicity by its antioxidant effect.